2016
DOI: 10.1371/journal.pone.0149840
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Creatine Supplementation during Pregnancy Prevents Long-Term Changes in Diaphragm Muscle Structure and Function after Birth Asphyxia

Abstract: Using a model of birth asphyxia, we previously reported significant structural and functional deficits in the diaphragm muscle in spiny mice, deficits that are prevented by supplementing the maternal diet with 5% creatine from mid-pregnancy. The long-term effects of this exposure are unknown. Pregnant spiny mice were fed control or 5% creatine-supplemented diet for the second half of pregnancy, and fetuses were delivered by caesarean section with or without 7.5 min of in-utero asphyxia. Surviving pups were rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…These included neurodegenerative disorders and myopathies (37). Indeed, in the spiny mouse model of birth asphyxia we have demonstrated that maternal creatine supplementation during gestation also minimizes neural injury (17), damage to the diaphragm muscle (18,38) and deleterious remodeling of the skeletal musculature (39).…”
Section: Discussionmentioning
confidence: 90%
“…These included neurodegenerative disorders and myopathies (37). Indeed, in the spiny mouse model of birth asphyxia we have demonstrated that maternal creatine supplementation during gestation also minimizes neural injury (17), damage to the diaphragm muscle (18,38) and deleterious remodeling of the skeletal musculature (39).…”
Section: Discussionmentioning
confidence: 90%
“…Intrapartum asphyxia was induced at 38 days of gestation (term at 39 days) as previously described [17][18][19][20][21][22]. Briefly, pregnant dams were killed via cervical dislocation.…”
Section: Housing Facility and Animal Carementioning
confidence: 99%
“…This study used the precocial spiny mouse to study the effects of intrapartum asphyxia on the brain [17][18][19][20][21][22]. The spiny mouse differs from conventional laboratory rodents (mice, rats) in that considerable brain maturation (including the beginnings of myelination) occurs in utero before birth [47]; hence, acute hypoxia delivered during the intrapartum period can be used as a model of oxygen starvation that occurs at birth in some human pregnancies.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A particular benefit in relation to CP is not only the decrease in severity of brain damage, but also the protection of skeletal muscle fibres and improved resistance to fatigue in the diaphragm (LaRosa et al . ). Neonatal acute kidney injury, which has a high prevalence in neonates that have experienced intrapartum hypoxia and is a co‐morbidity associated with poor neurological outcomes due to the acid–base and electrolyte imbalance (Perlman et al .…”
Section: Introductionmentioning
confidence: 97%